Experiments in game-projects in becoming with mathematics: transcribing the event - Almeida, Judá Rodrigues Braga de; Soares, Guilherme Araújo; Pinheiro, Jessica Melissa de Souza; Silva, Domingos Anselmo Moura da (JRG Journal of Academic Studies, 2024)
The aim is to translate the pedagogical experiments derived from the game-project into mathematics, offering reflections based on mathematical concepts through game-projects. Methodologically, this process is characterized by cartographic movements that use the researcher's notes, filming and student reports as tools for capturing data. During the creation and production of the games, signs are not merely employed or applied; they are reinvented, recontextualized and transformed. This process reveals that learning is a constant flow of innovation and emergence, always in process and never fixed. The students' creations emerged in two game projects that intertwine the History of Mathematics and fundamental operations. In this way, we open the door to a math education that continually reinvents itself, where teaching and learning become acts of producing meaning and difference. Each educational experience unfolds as an event of creation, where experimentation is the core of the educational process and learning is a practice of constant production and reconfiguration